Investigation of mechanical and wear behavior of Al based SiC reinforce metal matrix composite. (2020) - Kumar Yadav, Rakesh; Hasan, Zahir; Husain Ansari, Akhter
Abstract: The economy is significant element these days in the market. The examines are assuming a significant job in building field to expand the life of machine parts/segments & diminishing the expense. The composite materials can possibly supplant broadly utilized steel and aluminum because of their great qualities with better execution. Today, aluminum is used excessively across a wide range of domains, including domestic, transportation, land, sea, air and industry. Aluminum can be used purely or as an alloy by combining it with a variety of other elements such as copper, magnesium, manganese, silicon and zinc etc. Each element gives the alloy different characteristics and its composition has a varying effect on the alloy's mechanical properties. Morphological investigations of Al, SiC and Fe by SEM. The present examination depends on investigation of the impact of particulate stage on Micro hardness, Modulus of Elasticity & wear characteristics of Al as base material and Silicon Carbide & Ferrous as reinforcement composites. The microhardness & Elastic Modulus of the specimen is increased from 63 to 71 and 687 MPa to 720 MPa respectively with increasing the percentage of silicon carbide from 5 to 15%. The different outcomes induced from the tests are investigated and exposed to correlation with one another in this examination.